EFEKTIVITAS METODE JARIMATIKA UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG KELAS II SD NEGERI 0104 SIBUHUAN - Harahap, Nurhalimah; Daulay, Irma Sari; Tambunan, Miska Rizki (Yayasan Perguruan Kampus, 2025)
This study aims to: (1) To determine the application of the jarimatika method in class II of SD Negeri 0104 Sibuhuan. (2) To determine the arithmetic ability of class II students of SD Negeri 0104 Sibuhuan. Based on the results of the study, it can be concluded that: (1) The arithmetic ability of class II students of SD Negeri 0104 Sibuhuan in the pre-cycle is still low. This can be seen from the results of observations that have been carried out, in the pre-cycle the average value of arithmetic ability obtained by students is 58.07, the arithmetic ability of students with the category